2015
DOI: 10.3109/00952990.2015.1105242
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use/cessation expectancies and marijuana use in college students

Abstract: Background Research suggests that marijuana expectancies are associated with problematic marijuana use; however, these marijuana-related cognitions remain relatively understudied. Objective This study examined marijuana-related decision-making among college students by exploring the relationships among marijuana expectancies and marijuana use variables. Method College students (N = 357) endorsing lifetime marijuana use completed an online survey on marijuana use expectancies, marijuana cessation expectanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Therefore, the study addressed three key questions: is age of MJ use onset or cumulative MJ use associated with 1) self-reported changes in depression, anxiety, or sleep quality over monitored abstinence, 2) changes in MJ use expectancies, withdrawal, and craving over monitored abstinence, or 3) reward sensitivity and attentional impulsivity. We also examined if change in MJ use expectancies was related to change in emotional distress over monitored abstinence, given the increasing attention to how beliefs about marijuana use may distinctly influence treatment outcomes and use patterns (Brackenbury et al 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the study addressed three key questions: is age of MJ use onset or cumulative MJ use associated with 1) self-reported changes in depression, anxiety, or sleep quality over monitored abstinence, 2) changes in MJ use expectancies, withdrawal, and craving over monitored abstinence, or 3) reward sensitivity and attentional impulsivity. We also examined if change in MJ use expectancies was related to change in emotional distress over monitored abstinence, given the increasing attention to how beliefs about marijuana use may distinctly influence treatment outcomes and use patterns (Brackenbury et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…2006; Copeland et al 2016; Kaminer et al 2014; Schuster et al 2016; Stanger et al 2009). Limited work pointedly explores how a monitored abstinence protocol with adolescents simultaneously influences trajectories of subsyndromal mental health symptoms (e.g., depression and anxiety), sleep disturbance, marijuana use expectancies and consequences, and reward sensitivity in non-treatment seeking marijuana users compared to matched controls (Angarita et al 2016; Boden et al 2013; Brackenbury et al 2016; Gates et al 2016; Hayaki et al 2010; Moitra et al 2016; Moitra et al 2015). Barriers to treatment success (e.g., CM) may be associated with cannabis-related problems (e.g., withdrawal and craving) and processes that can influence emotional processing (e.g., negative affect), cognitive attributions and self efficacy (e.g., marijuana effect expectancies), and risk taking behaviors (e.g., continued use and functional consequences) (Budney et al 2001; Cornelius et al 2008; Fox et al 2011; Khurana et al 2015; Stanger et al 2013; Tims et al 2002; Zvolensky et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous research, results from this study provide support to the notion that youth who perceive undesired or unpleasant effects of cannabis consumption are less likely engaged in problematic cannabis use. In fact, a large body of cross-sectional and longitudinal research ( 20 , 22 , 54 , 55 ) found a significant negative relationship between negative cannabis use expectancies and the frequency of cannabis use, thus confirming that the endorsement of negative use expectancies may protect from involvement in cannabis use. Moreover, it could be hypothesized that negative effects expectancies about the potential effects of cannabis consumption may further reinforce the high levels of fearful traits characterizing socially anxious youth.…”
Section: Discussionmentioning
confidence: 92%
“…Expectancies regarding the effects of substance use have proved to be a promising area in explaining the link between SA disorder and substance use. According to social learning models of addiction, expectancies are defined as beliefs and attitudes regarding the effects of a given substance and represent an important construct to explain initiation, maintenance, and cessation of substance consumption ( 18 – 20 ). Positive attitudes or expectancies concerning substance or alcohol use during adolescence and youth seem to be predictive of current and subsequent substance use or problematic involvement ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation